Electrochemical impedance: A new alternative to assess the soap removal from biodiesel in the washing process. (1st April 2020) - Díaz-Ballote, L.; Maldonado, L.; Genesca, J.; Hoil-Canul, E.R.; Vega-Lizama, T.
Graphical abstract: Highlights: Novel application of impedance to determine the satisfactory soap limit in biodiesel. At least 5 GΩ·cm 2 is required to fulfill the maximum amount of soap in biodiesel. A decrease in the biodiesel soap content causes an increase in biodiesel resistance. Purification of biodiesel can be studied using impedance measurements. Impedance: a greener method for determining the threshold limit for soap in biodiesel. Abstract: An impedance- based sensor was built with stainless steel circular plates (7.0 cm 2 ) to evaluate the soap limit for both biodiesels produced from commercial soybean oil and from waste cooking oil. Conversion of soybean oil to biodiesel was achieved with KOH and waste cooking oil was converted to biodiesel using NaOH. Various biodiesel batches were dry washed using a mixed ionic resin to remove charged carriers such as soaps. Based on the Nyquist and Bode plots as well as the physical shape of the sensor, an Rb Cb parallel circuit was used for modelling the experimental data. It was found that washing had a significant effect on Rb in comparison with the effect on Cb . From the impedance data acquired using the present sensor, an Rb value of 5 GΩ·cm 2 was chosen as the minimum biodiesel resistance to assure a soap limit of below 41 ppm to comply with the currently accepted soap level in biodiesel.